2018
DOI: 10.1002/ppul.24180
|View full text |Cite
|
Sign up to set email alerts
|

Airway and esophageal eosinophils in children with severe uncontrolled asthma

Abstract: Aim Children with severe uncontrolled asthma (SUA) have a high burden of symptoms and increased frequency of asthma exacerbations. Reflux esophagitis and eosinophilic esophagitis are important co‐morbid factors for SUA. Both are associated with the presence of eosinophils in esophageal mucosa. We hypothesized that esophageal eosinophils are frequently present and correlate with the presence of airway eosinophils in children with SUA. Method We performed a retrospective analysis of a prospective database of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sputum neutrophils were higher in subjects with uncontrolled asthma, whereas eosinophils predominated in subjects with better‐controlled asthma, reinforcing the concept that neutrophil‐dominant inflammation may characterize an asthma phenotype of special concern . The second study by Ekman et al demonstrated that some children with severe persistent asthma have eosinophilic esophagitis (n = 3) or reflux esophagitis (n = 8). In these children, airway and esophageal eosinophils were correlated.…”
Section: Introductionmentioning
confidence: 86%
“…Sputum neutrophils were higher in subjects with uncontrolled asthma, whereas eosinophils predominated in subjects with better‐controlled asthma, reinforcing the concept that neutrophil‐dominant inflammation may characterize an asthma phenotype of special concern . The second study by Ekman et al demonstrated that some children with severe persistent asthma have eosinophilic esophagitis (n = 3) or reflux esophagitis (n = 8). In these children, airway and esophageal eosinophils were correlated.…”
Section: Introductionmentioning
confidence: 86%
“…Type 2 inflammation may be considered as an underlying immunopathological driver of atopic dermatitis. Hazard ratio: 1.7 and 40.0% (data from 2 studies) 102,103 Hazard ratio: 1.9 and 13.0% (data from 2 studies) 103,104 Children with atopic dermatitis 13.1-36.0% (data from 10 studies) 22,68,78,84,93,103,[105][106][107][108] 4.0-61.0% (data from 6 studies) 22,68,78,93,102,103 Hazard ratio: 3.2 (data from 1 study) 103 Children with chronic rhinitis 24.7-59.0% (data from 4 studies) 22,63,68,102 4.0-53% (data from 4 studies) 22,63,68,102 Hazard ratio: 2.8 (data from 1 study) 103 Children with eosinophilic esophagitis 45.4-59.8% (data from 3 studies)…”
Section: Respiratory Subgroupmentioning
confidence: 99%
“…Although most connective tissue diseases, such as eosinophilic granulomatosis with polyangiitis, lupus erythematodes, rheumatoid arthritis, systemic sclerosis, Sjögren syndrome, or scleromyositis may cause tissue eosinophilia in the GI tract, it occurs mostly in the small bowel, stomach, or colon [135, Peripheral blood eosinophils > 1500 cells/ml without secondary causes and evidence of an eosinophil-mediated end organ manifestation Atopic diseases (Asthma, aspirin-exacerbated respiratory disease, IgE mediated food allergy) [152,153] Extraintestinal manifestations Drug hypersensitivity and pill esophagitis Medical history Radiofrequency ablation for Barrett's esophagus [154][155][156] Typically without dysphagia Graft-versus-host disease [157] Eosinophil density correlates with GvHR Oral immunotherapy [158] Mostly transient and without symptoms Asymptomatic esophageal eosinophilia [159][160][161][162] Exclusive diagnosis 136]. An esophageal involvement is a rarity [136,137] and as opposed to EoE, most patients are female, have no atopy, and present with peripheral eosinophilia [136].…”
Section: Autoimmune Connective Tissue Diseasementioning
confidence: 99%